Безробіття в Україні та шляхи його подолання - Сокирко, Олена Сергіївна; Sokyrko, Olena Serhiivna (Науковий вісник Херсонського державного університету, 2018)
У статті охарактеризовано сутність безробіття, його значення і вплив на економіку України. Визначено, що воно є однією із найгостріших соціально-економічних проблем розвитку сучасної української економіки. Безробіття може виникати внаслідок як об’єктивних, так і суб’єктивних причин. Наразі воно є не лише економічною, а й соціальною проблемою, яку терміново необхідно вирішувати. В Україні безробіття носить масовий характер, що спричиняє досить значну міграцію робочої сили. Разом з тим у статті проведено аналіз рівня безробіття в Україні, а також наведено динаміку попиту і пропозиції робочої сили в Україні протягом останніх років. Визначено основні чинники формування безробіття та наведені наслідки, які несуть вплив на це явище. Розроблено пропозиції стосовно основних шляхів вирішення проблеми безробіття та цілеспрямованості активного підвищення рівня зайнятості населення України.

The article analyzes the essence of unemployment. The basic factors of formation and the consequences, which influence this phenomenon, are determined. Analysis of the unemployment rate in Ukraine, as well as the dynamics of demand and supply of labor force in Ukraine, is conducted, Proposals have been worked out on the main ways of solving the problem of unemployment and the purposefulness of the active increase of the employment rate of the population of Ukraine. In today's market conditions, unemployment is becoming an extremely acute problem in Ukraine. The current state of the Ukrainian economy does not give any hope of improving the situation on the labor market. Forecasts of experts are disappointing: the number of unemployed Ukrainians will grow. The economic crisis in Ukraine has a detrimental effect on employment in the country. That is why the study of unemployment in today's economic conditions for Ukraine is extremely relevant. Most economists and sociologists view unemployment as social evil. It is with unemployment that such destructive phenomena as decline in production, poverty, social tension, and criminalization are associated. Unemployment is a multifactor phenomenon that affects all spheres of public life and well-being of the population. Unemployment is considered a macroeconomic problem, which leads to many negative consequences in the state such as: increasing social differentiation, reducing labor activity of the population, increasing crime cases, increasing the cost of helping all the unemployed and, most importantly, reducing the gross domestic product of the country. There are a lot of reasons for unemployment, among which are: economic downturn, structural changes, technological progress and the introduction of new technologies. First of all, this is due to scarce investments, low level of introduction of modern technologies into the economy.
Unemployment in Ukraine and ways to overcome it
Keywords: безробіття; робоча сила; макроекономічна проблема; ринок праці; зайнятість; світовий досвід; державне благополуччя; unemployment; labor force; macroeconomic problem; labor market; employment; world experience; state welfare